Effect of different structures fabricated by additive manufacturing on bone ingrowth. (May 2022) - Lu, Shunyi; Jiang, Dongjie; Liu, Shuhao; Liang, Haifeng; Lu, Junren; Xu, Hao; Li, Juan; Xiao, Jian; Zhang, Jian; Fei, Qinming
Objective: To study the effects of different structures (solid/hollow) and pore diameters (300/600 μm) on bone ingrowth. Methods: Porous titanium alloy scaffolds (3.2 * 10.5 mm) were printed using electron beam melting. The implants were divided into either Hollow or Solid Group. The upper half of each implant was printed with a pore diameter of 600 μm while the bottom half was printed with a pore diameter of 300 μm. Visualization of the structural morphology was done using Scanning Electron Microscope (SEM). Cell proliferation was evaluated with the cell counting kit-8 assay and live/dead staining assay. The different lateral femoral condyles of 15 New Zealand rabbits were implanted with different groups of scaffolds. The rabbits were randomly sacrificed at the 4th, 8th, and 12th week postoperatively. Bone mineral density (BMD) and bone volume fraction (BV/TV) evaluation was completed by quantitative Micro-Computed Tomography (Micro-CT). Tissue histology were stained with toluidine blue to observe bone ingrowth under an optical microscope, and the percentage of new bone area were calculated using Image Pro-Plus 6.0. Results: SEM images showed a significant decrease in residual powder in the hollow implant and cell studies showed no obvious cytotoxicity for the Ti6 Al4 V scaffolds. Micro-CT reconstruction revealed high levels of new bone formation around the scaffolds. The trabeculae around the implants showed a gradual increase with each week, and new bone filled the scaffold pores gradually. BMD, BV/TV, and tissue histology revealed the 300 μm pore diameter is more conducive to bone ingrowth than the 600 μm ( p < .05). Conclusion: Our study revealed that Ti6 Al4 V implants with hollow structure could reduce the residual metal powder and implants with 300 μm pore diameter were more effective on bone formation than a 600 μm.